A direct role for cohesin in gene regulation and ecdysone response in Drosophila salivary glands. - Pauli, A; van Bemmel, J; Oliveira, R; Itoh, T; Shirahige, K; van Steensel, B; Nasmyth, K (2010)
BACKGROUND: Developmental abnormalities observed in Cornelia de Lange syndrome have been genetically linked to mutations in the cohesin machinery. These and other recent experimental findings have led to the suggestion that cohesin, in addition to its canonical function of mediating sister chromatid cohesion, might also be involved in regulating gene expression. RESULTS: We report that cleavage of cohesin's kleisin subunit in postmitotic Drosophila salivary glands induces major changes in the transcript levels of many genes. Kinetic analyses of changes in transcript levels upon cohesin cleavage reveal that a subset of genes responds to cohesin cleavage within a few hours. In addition, cohesin binds to most of these loci, suggesting that cohesin is directly regulating their expression. Among these genes are several that are regulated by the steroid hormone ecdysone. Cytological visualization of transcription at selected ecdysone-responsive genes reveals that puffing at Eip74EF ceases within an hour or two of cohesin cleavage, long before any decline in ecdysone receptor could be detected at this locus. CONCLUSION: We conclude that cohesin regulates expression of a distinct set of genes, including those mediating the ecdysone response.